Thiazolidinediones and Fertility in Polycystic Ovary Syndrome (PCOS) - Pascal Froment; Philippe Touraine (PPAR Research)
Polycystic ovary syndrome (PCOS) is the most frequent cause of female infertility. The treatment of PCOS patients with insulin sensitizers, such as metformin or thiazolidinediones, increases the ovulation rate and the number of successful pregnancies. The positive action of the insulin-sensitizing treatments could be explained by a decrease in the peripheral insulin resistance but also by a direct action at the ovarian level. We report in this review different hypotheses of thiazolidinediones actions to improve PCOS (steroid secretion by ovarian cells ; insulin sensitivity in muscle and adipocyte and fat redistribution).